A non-genetic, cell cycle-dependent mechanism of platinum resistance in lung adenocarcinoma - Gonzalez Rajal, Alvaro; Marzec, Kamila A; McCloy, Rachael A; Nobis, Max; Chin, Venessa; Hastings, Jordan F; Lai, Kaitao; Kennerson, Marina; Hughes, William E; Vaghjiani, Vijesh; Timpson, Paul; Cain, Jason E; et al. (eLife, 2021)
We previously used a pulse-based in vitro assay to unveil targetable signalling pathways associated with innate cisplatin resistance in lung adenocarcinoma (Hastings et al., 2020). Here, we advanced this model system and identified a non-genetic mechanism of resistance that drives recovery and regrowth in a subset of cells. Using RNAseq and a suite of biosensors to track single-cell fates both in vitro and in vivo, we identified that early S phase cells have a greater ability to maintain proliferative capacity, which correlated with reduced DNA damage over multiple generations. In contrast, cells in G1, late S or those treated with PARP/RAD51 inhibitors, maintained higher levels of DNA damage and underwent prolonged S/G2 phase arrest and senescence. Combined with our previous work, these data indicate that there is a non-genetic mechanism of resistance in human lung adenocarcinoma that is dependent on the cell cycle stage at the time of cisplatin exposure.